Developing Fighting Technique Through Visualization (Revista de Artes Marciales Asiáticas, 2012)
Visualization is a training technique that involves creating a detailed mental “movie” of successful performance. This article describes a type of visualization called “mental rehearsal” and explains how it can be used to reinforce the neuromuscular pattern of proper fighting technique. Drawing on his experience as a professional fighter and college coach, his studies in sport psychology as a college student, and his exposure to mental training techniques at the U.S. Olympic Training Center, the author reveals how to use mental imagery to facilitate the mastery of martial art technique.